Mycobacterium leprae in Nine-Banded Armadillos (Dasypus novemcinctus), Ecuador - Daniel Romero-Alvarez; Manuel Calvopiña; Emily Cisneros-Vásquez; Daniel Garzon-Chavez; Alaine K. Warren; Lauren S. Bennett; Ritika R. Janapati; Carlos Bastidas-Caldes; Melanie Cabezas-Moreno; Jacobus H. de Waard; Daniela Silva-Martinod; Roxane Schaub; et al. (Emerging Infectious Diseases)
We found Mycobacterium leprae, the most common etiologic agent of Hansen disease or leprosy, in tissues from 9 (18.75%) of 48 nine-banded armadillos (Dasypus novemcinctus) collected across continental Ecuador. Finding evidence of a wildlife reservoir is the first step to recognizing leprosy zoonotic transmission pathway in Ecuador or elsewhere.